Therapeutic and prophylactic deletion of IL‐4Ra‐signaling ameliorates established ovalbumin induced allergic asthma. Issue 6 (30th January 2020) - Khumalo, Jermaine; Kirstein, Frank; Scibiorek, Martyna; Hadebe, Sabelo; Brombacher, Frank
Abstract: Background: Allergic asthma is a chronic inflammatory airway disease driven predominantly by a TH 2 immune response to environmental allergens. IL‐4Rα‐signaling is essential for driving TH 2‐type immunity to allergens. Anti‐TH 2 therapies have the potential to effectively reduce airway obstruction and inflammation in allergic asthma. Objective: We investigated potential therapeutic effects of selective inhibition of this pathway in mice with established allergic airway disease. We further investigated whether IL‐4Rα disruption in systemically sensitized mice can prevent the onset of the disease. Methods: We used Rosa creERT2 IL‐4Rα −/lox mice, a tamoxifen (TAM)‐inducible IL‐4Rα knockdown model to investigate the role of IL‐4/IL‐13 signaling prior to the onset of the disease and during the effector phase in the ovalbumin‐induced allergic airway disease. Results: Inducible deletion of IL‐4Rα demonstrated therapeutic effects, on established allergic airway disease, and prevented the development of ovalbumin‐induced airway hyperreactivity, eosinophilia, and goblet cell metaplasia in allergen‐sensitized mice. Interestingly, IL‐4Rα knockdown after allergic sensitization did not induce TH 17, a neutrophilic inflammatory response as observed in global IL‐4Rα‐deficient mice after intranasal allergen challenge. Conclusion: Abrogation of IL‐4Rα signaling after allergic sensitization would have significant therapeutic benefit for TH 2‐type allergic asthma. Abstract : Interleukin 4 receptor alpha (IL‐4Rα) is central in the initiation and maintenance of the TH 2 allergic airway disease. Temporal genetic deletion of the IL‐4Rα after sensitization reduced TH 2 disease by abrogating effector mechanisms such as CD11b + migratory DCs, TH 2‐associated cytokines, eosinophilia, mucus production, and AHR. Temporal genetic deletion of the IL‐4Rα in an established disease reduced CD11b + migratory DCs, eosinophilia, IgE, mucus production, AHR, but not TH 2‐associated cytokines. Global deletion of the IL‐4Rα induces CD103 + DCs, neutrophilia, and TH17 cytokines, underscoring the importance of temporal genetic deletion. Abbreviations: AHR, airway hyperresponsiveness; IL‐4Ra, interleukin 4 receptor alpha; RORt, RAR‐related orphan receptor gamma; STAT6, signal transducer and activator of transcription 6